Anti-Terrorism and Protection of Human Rights in Nigeria - Joshua, Samson Ayobami (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
he Northern Region- particularly the north east of Nigeria has been under the siege of fundamentalist jihadist sect, otherwise known as Boko Haram since 2009 till date. The entire region has become a theatre of genocide, bloodshed and insecurity. This study attempts to evaluate this obvious challenge to security of lives and property of individual victims vis-Ã -vis the existing laws enacted to protect the victims. The approach of this study is premised on the argument that terrorism ordinarily amounts to a crime against human rights; and an infraction on fundamental freedoms of individuals by stigmatizing, delegitimizing and dehumanizing the victims. Though, the Nigerian government has responded to the menace of terrorism by enacting anti-terrorism laws, yet these laws have attracted severe criticisms. This study is founded on both primary and secondary data to give it a practical outlook. Consequently, the study discovered that application of some provisions of anti-terrorism laws negatively impact on the promotion and protection of human rights guaranteed under the 1999 Constitution. The study advocates measures to stem the tide of human rights abuse.